ULTRASOUND VS. MAMMOGRAPHY IN EVALUATING SUSPICIOUS BREAST LESIONS - AKHUND , J; MEMON, SK; QAMBER, JH; RASHID, I; ELHAJ, AH; ALSHAMMARI , AD (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to compare the effectiveness of ultrasound and mammography in evaluating suspicious breast lesions and determine their respective diagnostic capabilities. A retrospective analysis was conducted at Khyber Teaching Hospital Peshawar over 6 months, from March 2021 to September 2021. The study included 100 patients with suspicious breast lesions who underwent ultrasound and mammography examinations. The demographic data, including age and breast density, were recorded. Both imaging modalities’ diagnostic accuracy, sensitivity, specificity, and positive predictive value were calculated. Statistical analysis was performed using appropriate tests. The analysis included 100 patients with an average age of 51.3 years. The breast density distribution was as follows: 20% dense, 35% scattered fibroglandular, 30% heterogeneously dense, and 15% extremely dense. Ultrasound demonstrated higher sensitivity (75%) than mammography (65%) in the study population. When stratified by age, ultrasound had higher sensitivity in all age groups, with the highest sensitivity observed in patients aged >60 years (85%). Regarding breast density, ultrasound showed higher sensitivity across all density categories, particularly in patients with dense breasts (80%) and heterogeneously dense breasts (85%). Our study findings suggest that ultrasound is a valuable imaging modality in evaluating suspicious breast lesions, offering higher sensitivity than mammography, especially in patients with dense breast tissue. Incorporating ultrasound as an adjunct to mammography can improve diagnostic accuracy and aid in the early detection of breast cancer. These results support the growing recognition of ultrasound as an important tool in breast cancer diagnosis and highlight the need for further research and collaboration to optimize its utilization in clinical practice.